Atelier, czyli tam i z powrotem. Ewolucja filmu studyjnego od czasów kina niemego do ery cyfrowej - Kalbarczyk, Kamil (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article explores the concept of studio filmmaking in the context of early Hollywood and a new incarnation of studio filmmaking in the age of digital visual effects. The author analyses the old studio era in terms of shaping the cinematic image (primarily compositing) and the meaning of the studio, understood as an atelier. Kalbarczyk argues that originally the final look of the film used to be achieved by blending all the shot elements in the physical space of the studio, while nowadays the final form is most often created in a virtual space, deepening the decentralization of the filmmaking process. The author argues that more than the atelier space, the new studio filmmaking concept would refer to the holistic way of thinking about cinema as a heterogeneous structure, not so much attained integrally through filming, but carefully constructed. Various dimensions of studio filmmaking are discussed using the following films: Sunrise: A Song of Two Humans (1927), Citizen Kane (1941), Everest (2015) and Avengers: Endgame (2019).